The effect of training intervention based on health belief model on self-care behaviors of women with gestational diabetes mellitus - Fatemeh Mohammadkhah; Amirhossein Kamyab; Babak Pezeshki; Samira Norouzrajabi; Ali Khani Jeihooni (Frontiers in Global Women's Health)
BackgroundGestational diabetes mellitus (GDM) is currently the most common complication of pregnancy, and the prevalence of undiagnosed hyperglycemia and overt diabetes in young women is increasing. In this regard, the present study aimed to investigate the effect of training intervention based on the health belief model of self-care behaviors in women with gestational diabetes.MethodsThe present study was an interventional study, which was conducted on 160 women with gestational diabetes (80 in the interventional group and 80 in the control group), who were under treatment in healthcare centers in the city of Fasa in Fars Province, Iran, in 2022–2023. The method was simple random sampling. The collecting data tools were demographic characteristics questionnaire (age, education, occupation, monthly income of the family, gestational age (in the week), and rank of pregnancy, a knowledge assessment questionnaire, a questionnaire based on the health belief model (perceived sensitivity, perceived severity, perceived advantages, and disadvantages, self-efficiency), and the self-care behaviors questionnaire. The questionnaires were completed before the intervention and 6 weeks after the intervention. The women in the intervention group received six sessions of 50–55 min. Fasting blood sugar level and blood sugar level 2 h after the meal, A1C hemoglobin, and the need for taking insulin and the required dosage were recorded. The data were analyzed using SPSS 24, Kolmogorov-Smirnov tests (for normal distribution of data), independent t-test, paired t-test, chi-2 test, and descriptive statistics (P < 0.05).ResultsThe mean age of the participants in the intervention group and control group was 32.45 ± 4.82 and 33.16 ± 4.69, respectively. The results showed that the mean scores of all structures of the health belief model in the intervention group were significantly different from those obtained after the intervention in this group (p < 0.001). Also, the comparison of averages of blood sugar levels after the intervention in the two groups indicated that fasting blood sugar level, A1C hemoglobin, and blood sugar levels measured 2 h after the meal significantly decreased in the intervention group (p < 0.001). The need to increase the dosage of insulin in the intervention group was lower than in the control group.Conclusionsaccording to the results, the health belief model was effective in improving clinical results of self-care behaviors in women with gestational diabetes. HBM played an important role in understanding what care and support the women need. Therefore, the incidence of various diseases can be prevented and mothers with GDM can experience such vulnerability less than before. It can also be used as a model to design, implement, and monitor health programs for women with gestational diabetes.